Periódicos lançados por editoras: o caso do Boletim de Ariel (1931-1939) - Luca., Tania Regina De (Universidade Estadual Paulista Julio de Mesquita Filho, 2017)
Abstract The aim of this article is to analyze the practices adopted by publishers to broaden the circuit of diffusion of books, which could include the direct presence in the retail through bookstores as the foundation of magazines. The example of Boletim de Ariel (1931-1939) is useful to highlight the importance of this kind of publication, still little explored by the historiography, for the understanding of the tensions that crossed the intellectual world of the period.

Resumo O artigo tem por objetivo analisar as práticas adotadas por editores para ampliar o circuito de difusão de livros, o que tanto poderia incluir a presença direta no varejo, por meio de livrarias, quanto a fundação de revistas. Utiliza-se o exemplo do Boletim de Ariel (1931-1939) para evidenciar a importância desse tipo de publicação, ainda pouco explorada pela historiografia, para a compreensão das tensões que atravessavam o mundo intelectual do período.
Periodicals released by publishers: the example of Boletim de Ariel (1931-1939)
Keywords: Publishers; bookstores; magazines; Boletim de Ariel; Editores; livrarias; revistas; Boletim de Ariel